Silencing an aphid-specific gene SmDSR33 for aphid control through plant-mediated RNAi in wheat - Zhang, Jiahui; Li, Huiyuan; Zhong, Xue; Tian, Jinfu; Segers, Arnaud; Xia, Lanqin; Francis, Frédéric (Frontiers in Plant Science, 2023)
Grain aphid (Sitobion miscanthi) is one of the most dominant and devastating insect pests in wheat, which causes substantial losses to wheat production each year. Engineering transgenic plants expressing double strand RNA (dsRNA) targeting an insect-specific gene has been demonstrated to provide an alternative environmentally friendly strategy for aphid management through plant-mediated RNA interference (RNAi). Here we identified and characterized a novel potential RNAi target gene (SmDSR33) which was a gene encoding a putative salivary protein. We then generated stable transgenic wheat lines expressing dsRNA for targeted silencing of SmDSR33 in grain aphids through plant-mediated RNAi. After feeding on transgenic wheat plants expressing SmDSR33-dsRNA, the attenuated expression levels of SmDSR33 in aphids were observed when compared to aphids feeding on wild-type plants. The decreased SmDSR33 expression levels thus resulted in significantly reduced fecundity and survival, and decreased reproduction of aphids. We also observed altered aphid feeding behaviors such as longer duration of intercellular stylet pathway and shorter duration of passive ingestion in electropenetrography assays. Furthermore, both the surviving aphids and their offspring exhibited decreased survival rates and fecundity, indicating that the silencing effect could be persistent and transgenerational in grain aphids. The results demonstrated that SmDSR33 can be selected as an effective RNAi target for wheat aphid control. Silencing of an essential salivary protein gene involved in ingestion through plant-mediated RNAi could be exploited as an effective strategy for aphid control in wheat.